Electrolyte and secondary battery comprising the same
Patent Information
- Application Number
- CN202611328787.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-30
AI Technical Summary
然而,随着工作电压的提高,负极电势进一步降低,这对电解液的耐还原性能提出了更高要求
本申请提供的电解液中包括化合物A,化合物A为羧酸甲酯化合物。常见的羧酸酯通常在高温下会发生还原性脱羧、酯交换等副反应,这些副反应会生成短链羧酸、醇、烯烃等具有腐蚀性或高反应活性的产物,进而侵蚀负极界面、破坏固体电解质界面膜并引发更多的电解液分解,形成恶性循环。本申请研究发现,相比于羧酸乙酯或羧酸丙酯类化合物,羧酸甲酯更不容易发生还原性脱羧、酯交换等副反应,在实际电池中更稳定。一方面虽然羧酸甲酯的α-H(酸侧链中直接与羰基相连的碳原子上的氢)酸性更强,还原性更强,α-H更容易被攻击,但是在羧酸甲酯得到电子后其α-C形成一个碳负离子,羧酸甲酯烷氧基(-OCH3)很短,发生分子内酯交换需要形成一个四元或五元环过渡态,而烷氧基更长的羧酸乙酯和羧酸丙酯形成环状过渡态的空间位阻更小,因此羧酸甲酯更不容易发生酯交换反应;另一方面羧酸乙酯和羧酸丙酯醇部分的β-H的转移也更容易发生,从而更容易生成烯烃和羧酸,而羧酸甲酯的醇部分的β-C(酯侧链中直接与O相连的碳原子后连接的碳原子)根本不存在,因为甲氧基(-OCH3)只有一个碳,因此分子内醇部分的β-H转移的路径是关闭的。电解液包括羧酸甲酯后上述副反应的发生概率显著降低,从源头上减少了腐蚀性副产物的生成,从而减少电解液的消耗以及副反应放热,有利于维持电池循环过程中的容量保持率,但是这也造成了羧酸甲酯参与成膜程度低的问题。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary batteries, and more specifically to an electrolyte and a secondary battery containing the electrolyte. Background Technology
[0002] Lithium-ion batteries, with their advantages of being environmentally friendly and having high energy density, have been widely used in electronic devices such as laptops, mobile phones, smartwatches, and new energy vehicles. As users' demands for battery life and performance continue to increase, the development of lithium-ion batteries with even higher energy and power densities has become an urgent need.
[0003] Increasing the operating voltage is an effective way to improve the energy density of lithium-ion batteries. However, as the operating voltage increases, the negative electrode potential decreases further, which places higher demands on the reduction resistance of the electrolyte. Conventional electrolyte systems in related technologies are prone to reduction decomposition at the negative electrode under high voltage conditions. On the one hand, this continuously consumes active lithium ions in the electrolyte and generates byproducts, leading to accelerated capacity retention degradation. On the other hand, the reduction decomposition reaction is often accompanied by a large amount of exothermic reaction, which can easily trigger thermal runaway under high temperature conditions, affecting the thermal stability of the battery. How to balance the cycle performance and thermal stability of the battery under high voltage conditions has become an urgent problem to be solved in this field. Summary of the Invention
[0004] The primary objective of this application is to provide an electrolyte that suppresses the reduction and decomposition of the electrolyte at the negative electrode under high voltage, thereby balancing the cycle performance and thermal stability of the battery.
[0005] Another object of this application is to provide a secondary battery containing the above-mentioned electrolyte.
[0006] The objective of this application is achieved through the following technical solution: According to an embodiment of this application, in a first aspect, an electrolyte is provided, the electrolyte comprising compound A and compound B, wherein, based on the total mass of the electrolyte, the mass content of compound A is a %, and the mass content of compound B is b %, satisfying: 3≤a≤60, 1≤b≤30; The compound A is a methyl carboxylic acid ester compound, including at least one of the substances represented by Formula I: Formula I Wherein, R1 is a fluorine-substituted or unsubstituted alkyl group having 2 to 6 carbon atoms; The compound B is a fluorosulfonamide compound, including at least one of the substances represented by Formula II: Formula II R2 and R3 each independently include at least one of the following groups, either fluorinated or unsubstituted: C1-C6 alkyl, C2-C6 alkenyl, C2-C6 alkynyl, phenyl, silyl, alkylsulfonyl, or fluorosulfonyl.
[0007] According to an embodiment of this application, in a second aspect, a secondary battery is also provided, comprising the electrolyte described in the first aspect.
[0008] The technical solution of this invention has the following advantages: The electrolyte provided in this application includes compound A, which is a methyl carboxylate compound. Common carboxylate esters typically undergo reductive decarboxylation and transesterification side reactions at high temperatures. These side reactions generate short-chain carboxylic acids, alcohols, alkenes, and other corrosive or highly reactive products, which in turn erode the negative electrode interface, damage the solid electrolyte interfacial film, and trigger further electrolyte decomposition, forming a vicious cycle. This application's research found that, compared to ethyl carboxylate or propyl carboxylate compounds, methyl carboxylate is less prone to reductive decarboxylation and transesterification side reactions, and is more stable in practical batteries. On the one hand, although the α-H (hydrogen atom on the carbon atom directly bonded to the carbonyl group in the acid side chain) of methyl carboxylate is more acidic and reducing, and its α-H is more easily attacked, after methyl carboxylate gains an electron, its α-C forms a carbanion. The alkoxy group (-OCH3) of methyl carboxylate is very short, and intramolecular transesterification requires the formation of a four- or five-membered ring transition state. In contrast, ethyl carboxylate and propyl carboxylate, with their longer alkoxy groups, have less steric hindrance in forming cyclic transition states, making methyl carboxylate less prone to transesterification. On the other hand, the transfer of β-H in the alcohol moiety of ethyl carboxylate and propyl carboxylate is also more likely to occur, thus more easily generating alkenes and carboxylic acids. The β-C (carbon atom attached to the carbon atom after the carbon atom directly bonded to O in the ester side chain) of the alcohol moiety of methyl carboxylate is not present at all, because the methoxy group (-OCH3) has only one carbon. Therefore, the pathway for β-H transfer in the alcohol moiety of methyl carboxylate is closed. Including methyl carboxylate in the electrolyte significantly reduces the probability of the aforementioned side reactions, thereby reducing the generation of corrosive byproducts from the source. This reduces electrolyte consumption and the exothermic side reactions, which is beneficial for maintaining the capacity retention rate during battery cycling. However, this also results in a low degree of participation of methyl carboxylate in film formation.
[0009] Therefore, the electrolyte provided in this application also includes compound B, which is a fluorosulfonamide compound. Compound B can form a stable interfacial film with compound A, inhibiting the continuous reduction and decomposition of the electrolyte on the surface of the negative electrode active material. Furthermore, compound A is more stable than other carboxylic acid esters and is less susceptible to the active substances generated by fluorosulfonamide compounds at high temperatures. While compound A has the advantage of low viscosity, which improves the wettability and kinetic performance of the electrolyte, its low boiling point makes it prone to vaporization and gas generation under furnace temperature testing conditions, posing a safety concern at high temperatures when used alone. Compound B, on the other hand, has a high boiling point, which can raise the overall boiling point of the electrolyte and effectively inhibit the vaporization behavior of compound A. The combination of the two compounds retains the excellent reduction resistance and low viscosity advantages of compound A, while the film-forming effect and high boiling point of compound B compensate for its high-temperature stability deficiency. This allows the electrolyte system to simultaneously achieve excellent cycle performance, kinetic performance, and thermal stability under high voltage conditions.
[0010] Additional aspects and advantages of the embodiments of this application will be described and shown in part in the following description, or illustrated by practice of the embodiments of this application. Detailed Implementation
[0011] The following embodiments are provided to better understand the present invention, but the following embodiments do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the scope of protection of the present invention.
[0012] With the trend of lithium-ion batteries developing towards higher voltages, carboxylic acid ester solvents (such as ethyl propionate and propyl propionate) widely used in conventional electrolytes are prone to side reactions such as reductive decarboxylation and transesterification during high-voltage cycling. These reactions continuously consume the electrolyte and generate corrosive or highly reactive products, which damage the structural integrity of the solid electrolyte interfacial film, leading to a decline in battery cycle performance. At the same time, they are accompanied by a large amount of heat release, which significantly increases the risk of battery thermal runaway.
[0013] To address the aforementioned problems in related technologies, according to embodiments of this application, in a first aspect, an electrolyte is provided. The electrolyte includes compound A and compound B, wherein, based on the total mass of the electrolyte, the mass content of compound A is a%, and the mass content of compound B is b%, satisfying: 3 ≤ a ≤ 60, 1 ≤ b ≤ 30.
[0014] Compound A is a methyl carboxylate compound, which refers to a carboxylic acid ester compound whose molecular structure contains a methyl ester group (-COOCH3). In the molecular structure of a methyl carboxylate compound, the alcohol side directly attached to the ester group is a methoxy group, meaning the alcohol side contains only one carbon atom. Compound A includes at least one of the substances shown in Formula I: Formula I Wherein, R1 is a 2-6 fluorinated or unsubstituted alkyl group; Compound B is a fluorosulfonamide compound, which is a compound containing a sulfonamide group (-SO2-N-) and at least one fluorine atom in its molecular structure. The sulfonamide group has high polarity and strong coordination ability, enabling it to adsorb onto the electrode surface or participate in the formation of an interfacial film. Compound B includes at least one of the substances represented by Formula II: Formula II R2 and R3 each independently include at least one of the following groups, either fluorinated or unsubstituted: C1-C6 alkyl, C2-C6 alkenyl, C2-C6 alkynyl, phenyl, silyl, alkylsulfonyl, or fluorosulfonyl.
[0015] This study found that methyl carboxylate is less prone to reductive decarboxylation and transesterification side reactions than ethyl carboxylate or propyl carboxylate, thus exhibiting higher stability in batteries. Specifically, although the α-H of methyl carboxylate is more acidic and easier to remove, and its α-C forms a carbanion after gaining electrons, its alkoxy (-OCH3) carbon chain is extremely short. Intramolecular transesterification requires a four- or five-membered ring transition state, which has high steric strain and is difficult to form stably. In contrast, the alkoxy carbon chains of ethyl carboxylate and propyl carboxylate are longer, resulting in less steric hindrance for forming such cyclic transition states, thus making their transesterification reactions easier. Furthermore, the β-H of ethyl carboxylate and propyl carboxylate readily undergoes intramolecular transfer, leading to byproducts such as alkenes and carboxylic acids. In contrast, the methoxy group of methyl carboxylate contains only one carbon atom, and the molecule lacks a β-C, completely closing the intramolecular β-H transfer reaction pathway. Because the aforementioned side reaction pathways are effectively suppressed, the probability of methyl carboxylate undergoing reducing side reactions is significantly reduced, thereby decreasing the generation of corrosive byproducts at the source. This reduces electrolyte consumption and exothermic side reactions, which is beneficial for maintaining capacity retention during battery cycling. However, precisely because of its low side reaction activity, the extent to which methyl carboxylate participates in film formation at the negative electrode interface is relatively limited. Furthermore, methyl carboxylate compounds typically have low boiling points and are prone to vaporization and gas generation under high-temperature furnace testing conditions, which may lead to insufficient high-temperature safety of the battery when used alone.
[0016] The electrolyte provided in this application also includes compound B, which is a fluorosulfonamide compound. Compound B can synergistically form a more stable interfacial protective layer on the negative electrode surface with compound A, effectively preventing direct contact between the electrolyte and the negative electrode active material, thereby inhibiting the occurrence of reduction decomposition reactions. Simultaneously, the fluorosulfonamide compound has a high boiling point, which can increase the overall boiling point of the electrolyte and effectively suppress the vaporization behavior of compound A under high-temperature conditions. Furthermore, the low viscosity of compound A can compensate for the high viscosity of the fluorosulfonamide compound, improving the wettability and kinetic performance of the electrolyte. Through the synergistic effect between the above components, the electrolyte of this application achieves comprehensive improvement in both thermal stability and cycle performance.
[0017] When the mass content of compound A is too low (<3%), the amount of methyl carboxylate in the electrolyte is insufficient, making it difficult to fully utilize its advantages and limiting its effect on improving battery cycle performance. When the mass content of compound A is too high (>60%), the proportion of methyl carboxylate in the electrolyte system is too large, which may lead to a lower overall boiling point of the electrolyte, making it prone to vaporization under high temperature conditions and affecting the thermal stability of the battery.
[0018] When the mass content b% of compound B is too low (<1%), the fluorosulfonamide content is insufficient to form a adequate protective film on the negative electrode surface, and its film-forming effect and its effect on raising the boiling point of the electrolyte are not significant. When the mass content b% of compound B is too high (>30%), the proportion of fluorosulfonamide in the electrolyte is too large. Since fluorosulfonamides usually have high viscosity, this may lead to an excessively high overall viscosity of the electrolyte, affecting the wetting effect of the electrolyte on the electrodes and separator, as well as the lithium-ion transport kinetics.
[0019] Therefore, by controlling the mass content a% of compound A within the range of 3% to 60% and the mass content b% of compound B within the range of 1% to 30%, the electrolyte can possess both appropriate amounts of reducing-resistant components and film-forming components, which is beneficial for simultaneously improving the battery's cycle performance and thermal stability. Preferably, controlling the mass content a% of compound A within the range of 5% to 40%, and / or controlling the mass content b% of compound B within the range of 3% to 20%, can further improve the battery's cycle performance and thermal stability.
[0020] For example, 'a' can be 3%, 5%, 8%, 10%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 45%, 50%, 55%, 60%, or a value within the range of any two of the above values. 'b' can be 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, or a value within the range of any two of the above values.
[0021] In one embodiment, the mass content a% of compound A and the mass content b% of compound B satisfy the following condition: 0.2 ≤ a / b ≤ 15.
[0022] By controlling the mass ratio of compound A to compound B, a / b, within the range of 0.2 to 15, the ratio between the reducing-resistant component and the film-forming component in the electrolyte can be kept in a reasonable balance range. This is beneficial for simultaneously leveraging the reducing resistance and low viscosity advantages of compound A and the film-forming and high-boiling-point characteristics of compound B, thus enabling the electrolyte to balance cycle performance, kinetic performance, and thermal stability.
[0023] For example, a / b can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.5, 3, 3.5, 4, 5, 6, 8, 10, 12, 15 or a value within the range of any two of the above values.
[0024] In one embodiment, the carboxylic acid methyl ester compound comprises at least one of Formulas 1-1 to 1-8: Preferred formulas include formulas 1-2 and / or 1-4.
[0025] In one embodiment, the fluorosulfonamide compound includes at least one of formulas 2-1 to 2-16: ; The preferred option includes Equation 2-1.
[0026] In one embodiment, the electrolyte further includes a first cyclic carbonate, which includes at least one of ethylene carbonate (EC), fluoroethylene carbonate (FEC), and difluoroethylene carbonate (DFEC), and the mass content of the first cyclic carbonate is c% based on the total mass of the electrolyte, satisfying: 12≤c≤30.
[0027] EC, FEC, and DFEC have high reduction potentials and can preferentially undergo reduction reactions on the negative electrode surface compared to other solvent components, forming a solid electrolyte interphase (SEI) film. The SEI film can effectively block direct contact between the electrolyte and the negative electrode active material, thereby inhibiting further reduction and decomposition of the electrolyte on the negative electrode surface and improving the cycle performance of the battery.
[0028] By controlling the mass content (c%) of the first cyclic carbonate within the range of 12% to 30%, the cycle performance can be improved while reducing the impact on battery impedance growth and kinetic performance, and reducing the decrease in furnace temperature performance caused by the decomposition of cyclic carbonate compounds at high temperature and high voltage.
[0029] For example, c can be 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, or a value within the range of any two of the above values.
[0030] In one embodiment, the electrolyte further includes a sulfur-containing compound. The sulfur-containing compound includes at least one of monocyclic, bicyclic, and tricyclic sulfur-containing compounds. The monocyclic sulfur-containing compound includes at least one of 1,3-propanesulfonate lactone, 1,3-propenesulfonate lactone, 4-methylvinyl sulfate, methylene disulfonate, and 1,4-butanesulfonate lactone. The bicyclic sulfur-containing compounds include vinyl disulfate and / or pentaerythritol bicyclic sulfate; The tricyclic sulfur-containing compounds include vinyl trisulfate and / or mannitol sulfate; In a preferred embodiment, the sulfur-containing compound includes at least two of monocyclic sulfur-containing compounds, bicyclic sulfur-containing compounds, and tricyclic sulfur-containing compounds.
[0031] Under high-rate charge and discharge conditions, the battery temperature rises significantly, which may lead to a more severe deterioration of the battery's high-temperature performance due to methyl carboxylate. The SEI film, rich in lithium sulfonate salts and formed by sulfur-containing compounds, exhibits excellent high-temperature stability, effectively suppressing side reactions and gas generation at high temperatures, and further improving the battery's high-rate performance, high-temperature performance, and thermal safety. When the electrolyte includes at least two of monocyclic, bicyclic, and tricyclic sulfur-containing compounds, the resulting SEI film exhibits even higher stability at high temperatures, is less prone to decomposition, and can continuously act as a physical barrier to protect the negative electrode from electrolyte corrosion, effectively suppressing side reaction heat generation, and further improving the battery's cycle performance and thermal safety under high-temperature conditions.
[0032] It should be noted that the mass content of each component in the electrolyte of this application can be obtained by conventional testing methods in the art, such as: using a press to squeeze the electrolyte out of the battery, and then testing the composition and content of the electrolyte by gas chromatography-mass spectrometry (GCMS).
[0033] According to an embodiment of this application, in a second aspect, a secondary battery is provided, comprising the electrolyte described above.
[0034] In one embodiment, the secondary battery further includes a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector. The negative electrode active layer includes a nitrogen-containing compound. The nitrogen-containing compound includes at least one of boron nitride, silicon nitride, aluminum nitride, and titanium nitride. The boron nitride includes at least one of hexagonal boron nitride, cubic boron nitride, rhombohedral boron nitride, and wurtzite boron nitride.
[0035] Nitrogen-containing compounds exhibit high thermal stability and heat dissipation performance. In the negative electrode, nitrogen-containing compounds can form a thermally conductive network, rapidly dissipating heat generated inside the battery, especially heat generated on the surface of the negative electrode active material due to side reactions. This delays the onset temperature of thermal runaway and helps improve battery safety under high-temperature conditions.
[0036] However, nitrogen-containing compounds are insulators, and their addition to the negative electrode active layer can hinder electron transport to some extent, potentially leading to a decrease in battery kinetic performance. Compound A, with its low viscosity and high ionic conductivity, can enhance the ion transport capacity of the electrolyte and improve battery kinetic performance. Therefore, while adding a nitrogen-containing compound to the negative electrode active layer improves thermal stability, compound A in the electrolyte compensates for the negative impact of the nitrogen-containing compound on electron transport by increasing ionic conductivity. The synergistic effect of both compounds allows the secondary battery to achieve both improved thermal stability and good kinetic performance.
[0037] In one embodiment, the nitrogen-containing compound includes boron nitride, and the boron nitride content is 0.05% to 5% based on the total mass of the negative electrode active layer.
[0038] When the mass content of nitrogen-containing compounds is too low (<0.05%), it is difficult for nitrogen-containing compounds to form a continuous and effective thermal conductive network in the negative electrode active layer. Their thermal conduction and heat dissipation effects are not significant, and their improvement on battery thermal stability is limited.
[0039] When the mass content of nitrogen-containing compounds is too high (>5%), since nitrogen-containing compounds are insulators, excessive nitrogen-containing compounds will significantly reduce the electronic conductivity of the negative electrode active layer and deteriorate the dynamic performance of the battery.
[0040] Therefore, controlling the mass content of nitrogen-containing compounds within the range of 0.05% to 5% can effectively improve thermal stability while reducing the adverse effects on kinetic performance caused by excessive nitrogen-containing compounds.
[0041] For example, based on the total mass of the negative electrode active layer, the mass content of nitrogen-containing compounds can be 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a value within the range of any two of the above values.
[0042] It should be noted that the mass content of nitrogen-containing compounds can be tested using inductively coupled plasma atomic emission spectrometry (ICP-AES) or energy dispersive spectroscopy (EDS). Specifically, powder from the negative electrode active layer is scraped from the negative electrode sheet, and the content of boron, aluminum, or titanium is determined using ICP-AES. The mass content of the nitrogen-containing compound is then calculated based on the mass fraction of each element in the nitrogen-containing compound.
[0043] In one embodiment, a plurality of grooves are provided on the surface of the negative electrode active layer away from the negative electrode current collector. A groove refers to a groove-like structure with a specific geometric shape formed on the surface of the negative electrode active layer by physical (laser wire bonding) or chemical methods. The cross-sectional shape of the groove can be rectangular, trapezoidal, arc-shaped, or V-shaped, etc.
[0044] By creating the aforementioned grooves on the surface of the negative electrode active layer, the groove structure increases the electrolyte storage space of the negative electrode, thereby increasing the content of compound A (methyl carboxylate compound) and compound B (fluorosulfonamide compound) in the negative electrode. This facilitates the further enhancement of the reduction resistance of compound A and the film-forming protective effect of compound B, better suppressing the reduction decomposition of the electrolyte on the negative electrode surface. Simultaneously, the groove structure allows the injected electrolyte to rapidly diffuse from the grooves on the negative electrode surface into the interior of the negative electrode active layer, shortening the electrolyte wetting path and improving the wetting effect on the negative electrode. This improved wetting effect allows compounds A and B to be more evenly distributed within the negative electrode active layer and at the interface, promoting the full synergistic effect of both compounds.
[0045] In terms of heat dissipation, the grooved structure increases the heat dissipation area of the negative electrode, which is beneficial for the removal of heat from inside the battery. The improved heat dissipation brought by the grooved structure works in conjunction with the thermally conductive network formed by nitrogen-containing compounds to jointly enhance the battery's heat dissipation capacity from two aspects: increasing the heat dissipation area and improving thermal conductivity. This further improves the battery's cycle performance and thermal safety under high-temperature conditions.
[0046] By controlling the width of the groove to 10 μm to 800 μm, the depth of the groove to 2 μm to 38 μm, and the spacing between the grooves to 0.1 mm to 15 mm along the arrangement direction of the grooves, the grooves' liquid storage, wetting improvement, and heat dissipation effects can be fully utilized without excessively damaging the stability of the negative electrode structure or significantly affecting the battery's energy density.
[0047] For example, the width of the groove can be 10 μm, 20 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, 800 μm, or a value within the range of any two of the above values. The depth of the groove can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm, or a value within the range of any two of the above values. The spacing between the grooves can be 0.1 mm, 0.2 mm, 0.3 mm, 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 6 mm, 7 mm, 10 mm, 12 mm, 15 mm, or a value within any two of the above ranges.
[0048] It should be noted that the width, depth, and spacing of the grooves can be measured using a scanning electron microscope or a laser confocal microscope. Specifically, a negative electrode sample is taken, and the cross-section containing the grooves is observed and imaged under a scanning electron microscope. Image analysis software is then used to measure the width, depth, and spacing between adjacent grooves. At least five grooves are randomly selected for measurement, and the average value is taken as the final result.
[0049] In one embodiment, the negative electrode sheet includes a first surface and a second surface disposed opposite to each other along its thickness direction. The negative electrode sheet is provided with a concave-convex structure, which includes a plurality of corresponding protrusions and depressions. The first surface is provided with the protrusions, and the second surface is provided with the depressions. The concave-convex structure can be formed by an embossing process, causing the negative electrode sheet to undergo plastic deformation, thereby forming protrusions and depressions on both sides respectively.
[0050] The concave-convex structure increases the specific surface area of the negative electrode. Simultaneously, the recessed areas create additional electrolyte storage space, increasing the electrolyte retention capacity of the cell. This also increases the content of compounds A and B in the electrolyte within the negative electrode, enhancing their synergistic effect. In terms of heat dissipation, the concave-convex structure increases the effective heat dissipation area of the negative electrode. Combined with the aforementioned thermally conductive network formed by nitrogen-containing compounds and the groove structure, this collectively improves the battery's heat dissipation capacity and thermal stability.
[0051] By controlling the height of the protrusions to 1 μm to 45 μm, the diameter of the protrusions to 0.1 mm to 15 mm, and the spacing between the protrusions to 0.2 mm to 16 mm, the liquid storage capacity, wetting effect, heat dissipation performance, structural stability, and manufacturability of the negative electrode can be balanced.
[0052] For example, the height of the protrusion can be 1 μm, 2 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm, 40 μm, 42 μm, 45 μm, or a value within any two of the above values. The diameter of the protrusion can be 0.1 mm, 0.2 mm, 0.5 mm, 0.8 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, or a value within any two of the above values. The spacing between the protrusions can be 0.2 mm, 0.3 mm, 0.5 mm, 0.8 mm, 1 mm, 1.2 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, or a value within the range of any two of the above values.
[0053] It should be noted that the height, diameter, and spacing of the protrusions can be tested using a 2.5D profilometer and / or scanning electron microscope. Specifically, a 2.5D profilometer and / or scanning electron microscope are used to perform non-contact scanning of the negative electrode surface to obtain three-dimensional protrusion data. The acquired protrusion data is then analyzed using an image processing system to extract the height, diameter, and spacing between adjacent protrusions. The height of a protrusion refers to the vertical distance from the highest point of the protrusion to the reference plane of the negative electrode. The spacing between protrusions refers to the shortest distance between the edges of adjacent protrusions. The diameter of the protrusion is the circumcircle diameter. The circumcircle diameter is the diameter of the smallest circle that can completely encompass the projected profile of the protrusion in a direction parallel to the negative electrode surface. For circular protrusions, the circumcircle diameter is the diameter of the circle itself; for elliptical or irregularly shaped protrusions, the circumcircle diameter is the diameter of the smallest circle that can enclose the projected profile of the protrusion. At least five protrusions are randomly selected for measurement, and the average value is taken as the final result.
[0054] The present application will be further described in detail below with reference to specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in this application. Where specific experimental steps or conditions are not specified in the embodiments and comparative examples, they can be performed according to the conventional experimental steps or conditions described in the literature in the art. Reagents or instruments used, unless otherwise specified, are all commercially available conventional reagent products.
[0055] It should be noted that, as a unit of measurement, part by mass refers to the mass proportion of a certain component in a mixture. For example, 1 part by mass can be 0.1g, 1g, 8g, 25g, 60g, 100g, or any other positive number.
[0056] Example 1 This embodiment provides a method for preparing a battery, including the following steps: Step 1: Preparation of the positive electrode sheet Lithium cobalt oxide (CCO) material, carbon black (CCO), and polyvinylidene fluoride (PVDF) (PVDF) binder were mixed in a weight ratio of 98:1.2:0.8. N-methylpyrrolidone (NMP) was added, and the mixture was thoroughly stirred under vacuum until a homogeneous CCO slurry was formed. The CCO slurry was then uniformly coated onto both surfaces of the aluminum foil used as the CCO current collector. The coated aluminum foil was dried, rolled, cut, cleaned, and fitted with tab adhesive to obtain the CCO sheet.
[0057] Step 2: Preparation of the negative electrode The negative electrode active material (85% graphite and 15% silicon carbide), conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were mixed in a weight ratio of 97:1:1.5:0.5. Deionized water was added, and the mixture was thoroughly stirred under vacuum until a uniform negative electrode slurry was formed. The negative electrode slurry was then uniformly coated onto both surfaces of the negative electrode current collector copper foil. The coated copper foil was dried, rolled, cut, cleaned, and fitted with tab adhesive to obtain the negative electrode sheet.
[0058] Step 3: Preparation of electrolyte In an argon-filled glove box (H2O < 0.01 ppm, O2 < 0.01 ppm), propylene carbonate (PC), propyl propionate (PP), and ethyl propionate (EP) were mixed uniformly at a mass ratio of 20:40:40. Then, 15% of the first cyclic carbonate (8% FEC and 7% EC based on the total mass of the electrolyte), 15% of fully dried lithium hexafluorophosphate (LiPF6 based on the total mass of the electrolyte), and after dissolution, compound A (see Table 1 for specific components) (a% based on the total mass of the electrolyte), compound B (see Table 1 for specific components) (b% based on the total mass of the electrolyte), 1,3,6-hexanetrionitrile (HTCN) (2% based on the total mass of the electrolyte), 1,3-propanesulfonate lactone (PS) (0.5% based on the total mass of the electrolyte), and succinate (SN) and adiponitrile (ADN) (1% based on the total mass of the electrolyte) were added. After stirring evenly and passing the tests for moisture and free acid, the desired electrolyte is obtained.
[0059] Step 4: Battery fabrication The positive electrode sheet obtained in the first step, the negative electrode sheet obtained in the second step, and a commercially available conventional separator are stacked in the order of positive electrode sheet, separator, and negative electrode sheet, and then wound to obtain a battery cell. The battery cell is placed in an outer packaging aluminum foil, and the electrolyte obtained in the third step is injected into the outer packaging. After vacuum sealing, settling, formation, shaping, and sorting processes, a lithium-ion battery is obtained. The battery's charge / discharge range is 3.0V~4.55V.
[0060] The preparation methods of Examples 2-7, 9, 11 and 12 are basically the same as those of Example 1. The differences are shown in Table 1.
[0061] The battery preparation method in Example 8 is basically the same as that in Example 1, except that in the preparation of the electrolyte in the third step, a first cyclic carbonate (16% FEC and 14% EC) is added based on 30% of the total mass of the electrolyte.
[0062] The battery preparation method in Example 10 is basically the same as that in Example 1, except that in the preparation of the electrolyte in the third step, a first cyclic carbonate (6.5% FEC and 5.5% EC) is added at 12% of the total mass of the electrolyte.
[0063] The battery preparation method in Example 13 is basically the same as that in Example 1, except that in the preparation of the electrolyte in the third step, a first cyclic carbonate (5.3% FEC and 4.7% EC) is added based on 10% of the total mass of the electrolyte.
[0064] The battery preparation method in Example 14 is basically the same as that in Example 1, except that in the preparation of the electrolyte in the third step, a first cyclic carbonate (17.6% FEC and 15.4% EC) is added based on 33% of the total mass of the electrolyte.
[0065] The battery preparation method in Example 15 is basically the same as that in Example 1, except that in the preparation of the electrolyte in the third step, a first cyclic carbonate (8% FEC, 7% EC and 1% DFEC) is added at 16% of the total mass of the electrolyte.
[0066] The battery preparation method in Example 16 is basically the same as that in Example 1, except that in the preparation of the electrolyte in the third step, a first cyclic carbonate (FEC) is added at 15% of the total mass of the electrolyte.
[0067] The battery preparation method in Example 17 is basically the same as that in Example 1, except that in the preparation of the electrolyte in the third step, a sulfur-containing compound PS and mannitol carbonate sulfate are added at a mass ratio of 1:2, based on 0.5% of the total mass of the electrolyte.
[0068] The battery preparation method in Example 18 is basically the same as that in Example 1, except that in the preparation of the electrolyte in the third step, 0.5% of the total mass of the electrolyte is added, consisting of sulfur-containing compound PS, pentaerythritol bicyclic sulfate and mannitol carbonate sulfate, in a mass ratio of 1:2:1.
[0069] Examples 19-26 are basically the same as the battery preparation method in Example 1, except that d% of a nitrogen-containing compound is added in the second step of preparing the negative electrode sheet. The specific components of the nitrogen-containing compound and the specific value of d are shown in Table 1. The sum of the weight ratio of the nitrogen-containing compound to the negative electrode active material in the negative electrode slurry is 97%.
[0070] Furthermore, in the second step of preparing the negative electrode sheet in Example 23, the rolled negative electrode sheet is placed in a laser wire bonding device to form several grooves on the surface of the negative electrode active layer away from the negative electrode current collector, resulting in a negative electrode sheet with grooves on its surface. The width of the grooves is 800 μm, the depth of the grooves is 2 μm, and the spacing between the grooves is 0.1 mm. In the third step of preparing the electrolyte, a first cyclic carbonate (FEC) is added at 15% of the total mass of the electrolyte.
[0071] In the second step of preparing the negative electrode sheet for the battery of Example 24, the rolled negative electrode sheet was placed in a laser wire bonding device, forming several grooves on the surface of the negative electrode active layer away from the negative electrode current collector, resulting in a negative electrode sheet with grooves on its surface. The width of the grooves was 100 μm, the depth of the grooves was 25 μm, and the spacing between the grooves was 5 mm. The negative electrode sheet was then processed with a special roller containing protrusions to create a concave-convex structure, making the height of the protrusions 15 μm, the diameter of the protrusions 2 mm, and the spacing between the protrusions 3 mm, ultimately obtaining the desired negative electrode sheet.
[0072] In the second step of preparing the negative electrode sheet, the rolled negative electrode sheet was processed with a special roller containing protrusions to create a concave-convex structure, so that the height of the protrusions was 1 μm, the diameter of the protrusions was 0.1 mm, and the spacing between the protrusions was 0.2 mm, thus obtaining the desired negative electrode sheet. In the third step of preparing the electrolyte, a first cyclic carbonate (DFEC) was added at 15% of the total mass of the electrolyte.
[0073] In the second step of preparing the negative electrode sheet for the battery of Example 26, the rolled negative electrode sheet is placed in a laser wire bonding device to form several grooves on the surface of the negative electrode active layer away from the negative electrode current collector, resulting in a negative electrode sheet with grooves on the surface. The width of the grooves is 100 μm, the depth of the grooves is 25 μm, and the spacing between the grooves is 5 mm. In the third step of preparing the electrolyte, 20% of the total mass of the electrolyte first cyclic carbonate (EC) is added, along with 0.5% of the total mass of the electrolyte sulfur-containing compound PS and mannitol carbonate sulfate, in a mass ratio of 1:2.
[0074] Table 1 Test case 1. Cyclic capacity retention test The batteries prepared in each embodiment and comparative example were charged to 4.55V at 45℃±2℃ with constant current and constant voltage at 1C (cutoff current 0.05C), left to stand for 5 minutes, and discharged to 3.0V at 1C as one cycle. The discharge capacity of the first cycle was C1, and the discharge capacity after 1000 cycles was C2. The capacity retention rate was C2 / C1×100%.
[0075] 2. Hot Box Safety Test The batteries of each embodiment and comparative example were discharged to 3V at 0.2C at 25°C, left to stand for 10 minutes, and then charged to 4.55V at constant current and constant voltage at 0.7C with a cutoff current of 0.05C. After full charging, the batteries were placed in a precisely temperature-controlled hot box and then heated to 130°C±2°C at a rate of (5±2)°C / min and maintained for 1 hour. The samples were observed to see if thermal runaway (such as smoke, fire, or explosion) occurred after the hot box test. If not, it was recorded that the sample passed the hot box safety test. 20 cells were tested for each embodiment or comparative example. The results showed the number of passes, P / 20T. For example, 15P / 20T means that 15 out of 20 cells passed.
[0076] 3. Ratio performance Under an environment of 25℃±2℃, the batteries prepared in each embodiment and comparative example were charged to 4.5V at 0.7C with a cutoff current of 0.05C, allowed to stand for 5 minutes, and then discharged at 0.2C to a cutoff voltage of 3.0V to obtain the 0.2C discharge capacity. They were then charged again at 0.7C to 4.5V with a cutoff current of 0.05C and discharged at 2.5C to a cutoff voltage of 3.0V to obtain the 2.5C discharge capacity. The rate performance was calculated using the following formula: Rate performance (%) = (2.5C discharge capacity / 0.2C discharge capacity) × 100%.
[0077] The test results are shown in Table 2.
[0078] Table 2 Based on the test results in the table above, compared with Comparative Examples 1 to 5, Examples 1 to 26 show significant improvements in overall performance in terms of rate performance, cycle capacity retention, and hot box safety test pass rate.
[0079] In Comparative Example 1, the mass content of compound A exceeded the upper limit, resulting in an excessively low overall boiling point of the electrolyte. Excessive vaporization at high temperatures led to a significant decrease in the hotbox throughput; simultaneously, the a / b ratio exceeded the upper limit, significantly deteriorating cycle performance. In Comparative Example 2, the mass content of compound A was below the lower limit, resulting in severely insufficient electrolyte resistance to reduction. Excessive reduction and decomposition occurred at the negative electrode, significantly reducing cycle capacity retention. Comparative Example 3 contained no compound A, lacking a component with reducing resistance. Although there was no vaporization problem, cycle performance was severely inadequate. Comparative Example 4 contained no compound B, lacking film-forming protection and boiling point-raising effects. Excessive vaporization of compound A at high temperatures and lack of interfacial protection caused a sharp drop in hotbox throughput and a significant deterioration in cycle performance. In Comparative Example 5, the mass content of compound B exceeded the upper limit, resulting in excessively high electrolyte viscosity and a significant reduction in rate performance.
[0080] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. An electrolyte, characterized in that, The electrolyte includes compound A and compound B. Based on the total mass of the electrolyte, the mass content of compound A is a%, and the mass content of compound B is b%, satisfying: 3≤a≤60, 1≤b≤30. The compound A is a methyl carboxylic acid ester compound, including at least one of the substances represented by Formula I: Formula I Wherein, R1 is a fluorine-substituted or unsubstituted alkyl group having 2 to 6 carbon atoms; The compound B is a fluorosulfonamide compound, including at least one of the substances represented by Formula II: Formula II R2 and R3 each independently include at least one of the following groups, either fluorinated or unsubstituted: C1-C6 alkyl, C2-C6 alkenyl, C2-C6 alkynyl, phenyl, silyl, alkylsulfonyl, or fluorosulfonyl.
2. The electrolyte according to claim 1, characterized in that, The condition 'a' and 'b' satisfy: 0.2 ≤ a / b ≤ 15; Preferably, 'a' satisfies: 5 ≤ a ≤ 40; and / or, 'b' satisfies: 3 ≤ b ≤ 20.
3. The electrolyte according to claim 1 or 2, characterized in that, The electrolyte further includes a first cyclic carbonate, which includes at least one of ethylene carbonate, fluoroethylene carbonate, and difluoroethylene carbonate. Based on the total mass of the electrolyte, the mass content of the first cyclic carbonate is c%, satisfying: 12≤c≤30.
4. The electrolyte according to claim 1 or 2, characterized in that, The electrolyte also includes sulfur-containing compounds, which include at least one of monocyclic sulfur-containing compounds, bicyclic sulfur-containing compounds, and tricyclic sulfur-containing compounds. The monocyclic sulfur-containing compound includes at least one of 1,3-propanesulfonate lactone, 1,3-propenesulfonate lactone, 4-methylvinyl sulfate, methylene disulfonate, and 1,4-butanesulfonate lactone. The bicyclic sulfur-containing compounds include vinyl disulfate and / or pentaerythritol bicyclic sulfate; The tricyclic sulfur-containing compounds include vinyl trisulfate and / or mannitol sulfate; Preferably, the sulfur-containing compound includes at least two of the following: monocyclic sulfur-containing compounds, bicyclic sulfur-containing compounds, and tricyclic sulfur-containing compounds.
5. The electrolyte according to claim 1, characterized in that, The methyl carboxylate compound includes at least one of Formulas 1-1 to 1-8: ; Preferred options include formulas 1-2.
6. The electrolyte according to claim 1, characterized in that, The fluorosulfonamide compound includes at least one of formulas 2-1 to 2-16: ; The preferred option includes Equation 2-1.
7. A secondary battery, characterized in that, The secondary battery includes the electrolyte according to any one of claims 1 to 6.
8. The secondary battery according to claim 7, characterized in that, The secondary battery further includes a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector, the negative electrode active layer including a nitrogen-containing compound. The nitrogen-containing compound includes at least one of boron nitride, silicon nitride, aluminum nitride, and titanium nitride; The boron nitride includes at least one of hexagonal boron nitride, cubic boron nitride, rhombohedral boron nitride, and wurtzite boron nitride.
9. The secondary battery according to claim 8, characterized in that, The nitrogen-containing compound includes boron nitride; and / or, based on the total mass of the negative electrode active layer, the mass content of the nitrogen-containing compound is 0.05% to 5%.
10. The secondary battery according to claim 8 or 9, characterized in that, The surface of the negative electrode active layer away from the negative electrode current collector is provided with a plurality of grooves; the width of the grooves is 10 μm to 800 μm, the depth of the grooves is 2 μm to 38 μm, and the spacing between the grooves is 0.1 mm to 15 mm along the arrangement direction of the grooves. And / or, the negative electrode includes a plurality of protrusions arranged along its thickness direction, the height of the protrusions being 1 μm to 45 μm, the diameter of the protrusions being 0.1 mm to 15 mm, and the spacing between the protrusions being 0.2 mm to 16 mm.